Synchrotron micro-CT scanning leads to the discovery of a new genus of morphologically conserved echinoid (Echinodermata: Cassiduloida) - Souto, Camilla; Martins, Luciana (Zootaxa, 2018)
Here we use synchrotron radiation-based micro-computed tomography (SRµCT) images of type specimens to confidently place Cassidulus malayanus in a new genus (Kassandrina gen. nov.) that would not have been discovered with traditional techniques, and to describe a new species of Cassidulus (Cassidulus briareus sp. nov.) from Australia and designate a neotype for Cassidulus caribaearum. We also provide remarks describing the taxonomic history of each taxon and a diagnostic table of all living cassidulid species, and extend the known geographic and bathymetric range of C. caribaearum and C. malayanus. Besides rendering novel morphological data, the SRµCT images provide significant insights in the evolution of bourrelets of these cassiduloid echinoids.